Aplikasi Sistem Pendukung Keputusan Metode TOPSIS dan AHP-TOPSIS Untuk Pemilihan Proyek Pada Perusahaan Kontraktor CV.X - Aldo Kurnia Christianto; Alexander Setiawan; Andreas Handojo (Universitas Kristen Petra, 2022)
A contractor company is an example of a company engaged in the construction sector. CV.X contractor companies need to consider project bids by considering all aspects of the company and appropriately. Inefficient project selection can be fatal. Project selection errors can occur because decision makers only rely on feelings and experiences. Therefore, a decision support system can help the decision-making process at the CV.X contractor company. The TOPSIS and AHP-TOPSIS methods are used to find out which method is better to be applied to a decision support system and make weight improvements after knowing the best method for each project category that CV.X is working on. In the construction/rehabilitation project category, AHP-TOPSIS is better than TOPSIS with a correlation coefficient of 0.8 for Kendall and 0.9 for Spearman. In the TOPSIS and AHP-TOPSIS road improvement project categories, the Kendall 1 and Spearman correlation coefficient values are 1. For the licensing project category, the TOPSIS method excels with the Kendall correlation coefficient value of 0.33 and Spearman 0.464286. TOPSIS weight improvement is done by brute force to find the combination of weights with the best correlation value. Improvements to the weight of the criteria were not carried out in the category of development/rehabilitation projects because the resulting ranking results were slightly different and were used as a reference for decision making. Improvements to the weighting criteria for the road improvement project category were not carried out. Improvements to the weighting criteria for the TOPSIS method permit project category were carried out and increased the resulting Kendall and Spearman correlation values to 0.714286 and 0.821429.